Is a World-Class University Possible in Rural Bihar? - Altbach, Philip G. (International Higher Education, 2013)
The Indian and Bihar government, with the support of the East Asian Summit, is resurrecting the 6th century Nalanda University, near its original site in rural northern Bihar. Significant funds have been earmarked for the project, and planning is now under way. Impressive international linkages have already been made. The concept, of course, is wonderful—to recreate in modern garb a true cultural and intellectual treasure of ancient India. The plan for the university focuses on the humanities, social sciences, ecology, and business studies—not the usual engineering and technology emphasis. But some serious practical and conceptual questions need to be asked.